Predictors of Intention to Interact with Apparel Products on Instagram: Do creativity and Positive Emotion Matter? - Wardana, Candra Kusuma; Prasetya, Farid Adi; Maimun, Muhammad Halim; Fatchan, Fuad Hudaya (Jurnal Manajemen Bisnis, 2024)
Research aims: This study aims to determine the effect of perceived creativity, positive emotion, affective commitment on people intention to interact.Design/Methodology/Approach: The study procedures were carried out using a quantitative approach and data were collected with online questionnaires from July to December in 2023. The participants were selected using purposive sampling based on specific criteria, such as experience in purchasing products online. A total of 225 participants were selected and analysis was performed using Structural Equation Modelling (SEM) approach with SmartPLS.Research findings: The results showed that perceived creativity had a significant relationship on positive emotion and affective commitment. Positive emotion was shown to have a significant effect on interaction intention. However, perceived creativity had no significant impact on interaction intention of apparel brand. This indicated that creative content was inadequate in attracting Instagram users to interact with brand’s account. The results also showed that positive emotion lacked a significant correlation with affective commitment, while affective commitment had a significant relationship with interaction intention.Theoretical Contribution/Originality: This study provides meaningful contribution to Stimulus-Organism-Response theory by incorporating creativity to assess Instagram social media platform.Practitioners/Policy Implications: These results can assist business owners and social media marketers in developing creative marketing campaigns and building strong bond with their followers.Research Limitations/Implications: One of the limitations of this study is that it only assessed the use of Instagram in the fashion industry. Therefore, future studies are advised to explore different industries and recruit participants with a specific occupation to obtain better understanding of online consumer behavior.